SOCIAL PARTICIPATION IN THE ASPECT OF A SMART CITY DEVELOPMENT - KOCUR-BERA, Katarzyna (GeoScience Engineering, 2019)
Advanced technologies are entering citizens’ lives, which can be noticed at every turn. Society is becoming increasingly involved in building, creating and planning a city, district or the nearest place of residence. The quality of the functioning of the local community and the quality of life depends, to a large extent, on the level of social participation. The aim of social participation is to establish a mechanism for meeting citizens’ needs and to achieve citizens’ acceptance of the authorities’ actions. Modern communication techniques greatly facilitate the expression of public opinion and public awareness in this regard has been on the rise. A growing number of new forms of communication using modern technologies are being developed all the time. The aim of the study is to analyze the forms of social participation in city life, inter alia spending financial resources on its development. Attention is also drawn to the most recent ways in which the authorities communicate with the public in order for the latter to express their opinions on the former’s actions. Practical research was conducted for the city of Olsztyn located in the north-eastern part of Poland. Social activity forms were analyzed, including those carried out using ICT technologies. The research shows that access to modern technologies facilitates contact between the city authorities and citizens, which ensures that the policy under implementation is kept in line with citizens’ expectations. Keywords: social participation, smart city, development DOI 10.35180/gse-2019-0016